2014
DOI: 10.1128/cvi.00622-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Bacillus subtilis Spores and Monophosphoryl Lipid A as Adjuvants of Protein-Based Mycobacterium tuberculosis-Based Vaccines: Partial Requirement for Interleukin-17A for Induction of Protective Immunity

Abstract: The development of adjuvants for vaccines has become an important area of research as the number of protein-based vaccines against infectious pathogens increases. Currently, there are a number of adjuvant-based Mycobacterium tuberculosis vaccines in clinical trials that have shown efficacy in animal models. Despite these novel adjuvants, there is still a need to design new and more versatile adjuvants that have minimal adverse side effects but produce robust long-lasting adaptive immune responses. To this end,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Similar to other studies our findings showed that MPL enhanced titers of both serum IgG1 and IgG2a antibody when administered subcutaneously or mucosally, indicative of a mixed type 1 (Th1) and type 2 (Th2) immune responses [17,[24][25][26][27]. It has been suggested that MPL enhanced antigen-specific humoral responses by recruiting antigenpresenting cells (APCs) and inducing increased surface expression of MHC and the costimulatory molecules [28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to other studies our findings showed that MPL enhanced titers of both serum IgG1 and IgG2a antibody when administered subcutaneously or mucosally, indicative of a mixed type 1 (Th1) and type 2 (Th2) immune responses [17,[24][25][26][27]. It has been suggested that MPL enhanced antigen-specific humoral responses by recruiting antigenpresenting cells (APCs) and inducing increased surface expression of MHC and the costimulatory molecules [28].…”
Section: Discussionsupporting
confidence: 89%
“…Immunization with MPL and vaccine antigens has been shown to result in a mixed Th1 and Th2 or a shift toward either Th1 or Th2 response and it has been suggested that in addition to the route of administration, variables such as strains of the mice used, type of antigens as well as the concentration of antigen and MPL may affect the Th1/Th2 phenotype [25,26,39,42,43]. Baldridge et al [13] showed that hepatitis B and influenza antigens formulated with MPL and administered IN produced significantly higher IgG2a than IgG1, whereas tetanus toxoid mixed with MPL induced a lower IgG2a than IgG1.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that IL-17 expression is up-regulated during M. tuberculosis infection, but the question remains as to the importance of this cytokine in vaccine mediated immunity. The importance of IL-17 may also depend on the type of vaccine used and, as we demonstrated, the requirement for IL-17 in an MPL based vaccine for induction of protective immunity was not absolute [23]. IL-10 mRNA expression was significantly up regulated in the spleens of ST28 inoculated animals and may reflect the ability of the mutant to prevent pathology in extra-pulmonary sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, if produced prior to infection, antibodies may become significant in prevention of infection. Vaccines studied in mice have reported induction of post-vaccination antibodies, but could not demonstrate contribution to protective immunity [33, 71] since no effect on the mycobacterial burden was seen despite antibody production to vaccine antigens [72]. This is also highlighted by the fact that maternal antibodies do not seem to play a role in protecting new born against infection, although maternal antibodies were shown to inhibit PPD-specific T cell responses in BCG vaccinated infants [73].…”
Section: Vaccine Induced Antibodies As a Means Of Preventing Infectionmentioning
confidence: 99%